2019
DOI: 10.1101/577544
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variation of human neural stem cells generating organizer statesin vitrobefore committing to cortical excitatory or inhibitory neuronal fates

Abstract: SUMMARYBetter understanding the progression of neural stem cells (NSCs) in the developing cerebral cortex is important for modeling neurogenesis and defining the pathogenesis of neuropsychiatric disorders. Here we used RNA-sequencing, cell imaging and lineage tracing of mouse and human in vitro NSCs to model the generation of cortical neuronal fates. We show that conserved signaling mechanisms regulate the acute transition from proliferative NSCs to c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 121 publications
0
11
0
Order By: Relevance
“…Our data and the recent identification of time- and lineage-specific eQTLs that influence differentiation (Cuomo et al, 2020) suggest that the interaction between constitutive and dynamic control of gene expression is central to the lineage decisions that underlie cell line-specific differentiation bias. SOX21 is highly represented in the neuroectoderm initiating pattern P15 and is differentially expressed across hPSC lines in both SR and NSB conditions (Figure 1E and S1G), suggesting it may play a key role in generating telencephalic organizer states preceding neurogenesis (Micali et al, 2020). Previously, we have shown that SOX21 is required for reprogramming to the pluripotent state and regulates the anterior-posterior identity in the adult mouse intestine (Kuzmichev et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our data and the recent identification of time- and lineage-specific eQTLs that influence differentiation (Cuomo et al, 2020) suggest that the interaction between constitutive and dynamic control of gene expression is central to the lineage decisions that underlie cell line-specific differentiation bias. SOX21 is highly represented in the neuroectoderm initiating pattern P15 and is differentially expressed across hPSC lines in both SR and NSB conditions (Figure 1E and S1G), suggesting it may play a key role in generating telencephalic organizer states preceding neurogenesis (Micali et al, 2020). Previously, we have shown that SOX21 is required for reprogramming to the pluripotent state and regulates the anterior-posterior identity in the adult mouse intestine (Kuzmichev et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Following the discovery of reprogramming factors (Takahashi and Yamanaka, 2006), functional heterogeneity in hiPSC differentiation potential has been a continuing focus of interest (Hu et al, 2010; Kanton et al, 2019; Mariani et al, 2015; Micali et al, 2020; Strano et al, 2020; Wang et al, 2020). Initial studies noted functional consequences of epigenetic memory of parental cell types in reprogrammed cells (Cahan and Daley, 2013; Kim et al, 2010; Kim et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it is of scientific interest to harness the collective discovery potential of such complex and growing data resources. For example, in biomedical research, high-dimensional gene expression and epigenetic data are produced to gain insight into cellular processes and disease mechanisms (Johnson et al, 2020; Micali et al, 2020; Clark et al, 2019; Stein-O’Brien et al, 2019). Another example is in the study of Alzheimer’s disease where recent efforts have been focusing on combining brain imaging data, genetic data, as well as clinical outcomes in predicting disease (Nathoo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%